The potential bene fits of surface corrugation and hybrid nanofluids in channel flow on the performance enhancement of a thermo-electric module in energy systems - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2020)
In the present work, combination of surface corrugation and use of hybrid nanofluid is offered as a novel method for performance enhancement of a thermoelectric generator module placed between channels which carry hot and cold fluid streams. The three dimensional coupled field equations are solved with finite element method. Impacts of Reynolds number (between 250 and 1000), number (between 1 and 8), height (between H/8 and H/1.75) and type (rectangular and circular) of the corrugation and solid particle volume fraction of the hybrid nanofluid (between 0 and 0.02) on the fluid flow, heat transfer and power features are examined. It is observed that the thermoelectric module power enhances with higher Reynolds number, solid volume fraction of the hybrid nanoparticles, height and number of waves in the surface corrugation. Rectangular and circular corrugation type is also found as influential on the flow and generated power features. The power rises by about 10.95% at Reynolds number of 250 while it is 7.50% at Reynolds number of 1000 at solid volume fraction of 0.02. Height of the corrugation has more impact on the generated power as compared to number of waves in the corrugation which are 17.3% and 19.6% for rectangular and circular type corrugation with the lowest and highest values of height. However, only 9.5% increment in the power is achieved for circular corrugation when lowest and highest number of waves are considered. A correlation for the generated power is developed which is a polynomial type and depends upon the Reynolds number and solid volume fraction of the hybrid nanoparticles. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Surface corrugation; Numerical simulation; Thermoelectric energy; Finite element method; Hybrid nanofluid